Inhibition of persimmon tannin extract on guinea pig skin pigmentation. (21st January 2021) - Sun, Wanting; Chen, Xuanhong; Nan, Xijun; Zhang, Jun; Dong, Leichao; Ji, Wei; Sheng, Guihua; Zhou, Quancheng
Abstract: Background: In daily life, excessive exposure to ultraviolet light can lead to pigmentation. Aims: This study is to determine the mechanism of persimmon tannin extract in inhibiting pigmentation, to investigate whether the effect of persimmon tannin extract is superior to that of arbutin, and to detect the optimal concentration. Methods: In this study, the guinea pig pigmentation model was established by ultraviolet B (UVB) irradiation. With arbutin as a positive control, Masson‐Fontana silver staining was used to observe the effects of persimmon tannin extract on melanin distribution in guinea pigs' skin tissue. Then, the tyrosinase activity was measured, and an Enzyme‐linked immunosorbent assay was used to investigate the contents of antioxidant enzymes, inflammatory factors, and signaling pathway inhibitors in guinea pigs' skin tissue. Results: The results showed that compared with the model group, superoxide dismutase, catalase, glutathione peroxidase, DKK1 content of Wnt/‐catenin signaling pathway inhibitors levels, and inhibitory tyrosinase activity were increased by 24.3%, 33.3%, 59.3%, 36.81%, and 17.16%, respectively. Meanwhile, the interleukin‐6 and interleukin‐8 expression were reduced by approximately 22.2% and 54%. The results also showed that persimmon tannin extract could significantly reduce melanin density. The differences in experimental results were statistically significant ( P < .01). Conclusions: Compared with the arbutin group, the medium‐dose group (persimmon tannin extract of 20%) had a more significant effect on inhibiting pigmentation. Persimmon tannin could serve as a promising agent for preventing skin pigmentation. It is expected to provide ideas for the development of deep‐processed persimmon products related to functional foods and cosmetics.